2017
DOI: 10.1002/mp.12606
|View full text |Cite
|
Sign up to set email alerts
|

Toward optimization of in vivo super‐resolution ultrasound imaging using size‐selected microbubble contrast agents

Abstract: Purpose Microvascular processes play key roles in many diseases including diabetes. Improved understanding of the microvascular changes involved in disease development could offer crucial insight into the relationship of these changes to disease pathogenesis. Super-resolution ultrasound (SR-US) imaging has showed the potential to visualize microvascular detail down to the capillary level (i.e., subwavelength resolution) but optimization is still necessary. The purpose of this study was to investigate in vivo S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…There is an inherent compromise between the SNR of the signal and the localization precision. This has been highlighted in studies such as Desailly et al (2015), Ghosh et al (2017), Lin et al (2017a) and Espindola et al (2018). Exploration of the impact of SNR, specifically in relation to depth and aberration effects, is greatly needed.…”
Section: Trade-offs and Limitationsmentioning
confidence: 82%
See 2 more Smart Citations
“…There is an inherent compromise between the SNR of the signal and the localization precision. This has been highlighted in studies such as Desailly et al (2015), Ghosh et al (2017), Lin et al (2017a) and Espindola et al (2018). Exploration of the impact of SNR, specifically in relation to depth and aberration effects, is greatly needed.…”
Section: Trade-offs and Limitationsmentioning
confidence: 82%
“…In Foiret et al (2017), the coherence factor, the ratio of coherent intensity to incoherent intensity (Mallart and Fink 1994), was applied to CPS images to improve the SNR of echoes from individual microbubbles. Ghosh et al (2017) and Lin et al (2017b) have reported that selecting a population of larger microbubbles improves the SNR from individual microbubbles. Finally, because of the challenge of separating bubble signals from noise in images using just spatial information, Song et al (2017) proposed to denoise the microbubble signal in a spatiotemporal domain using a nonlocal means filter to improve the separation of microbubble "tracks" from random background noise that does not resemble any feature or pattern.…”
Section: Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although US does not provide accurate absolute MB concentration, it does provide accurate relative difference in MB concentration between adjacent tissues within the same imaged field. Recently introduced sub-voxel resolution with MB suggests that an accurate MB count can potentially be provided over the entire field of view [33,34]. In addition to the same challenges as US, PAI also suffers from light attenuation that is different for each spectral wavelength.…”
Section: Overview Of Sc Imaging Technologiesmentioning
confidence: 99%
“…Microvascular processes play an important role in many diseases, such as diabetes . An improved understanding of these changes has the potential for providing novel insight into characterizing their relationship with developing pathologic conditions as a guide to more effective therapies . In 2016, Machado et al described a novel Superb Microvascular Imaging (SMI; Canon Medical Systems, Tustin, CA) technique for the assessment of thyroid vascularity.…”
mentioning
confidence: 99%